1984
DOI: 10.1056/nejm198401053100104
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Interferon for Induction of Remission in Hairy-Cell Leukemia

Abstract: We treated seven patients who had progressive hairy-cell leukemia with daily doses of 3 million units of partially pure alpha (leukocyte) interferon by the intramuscular route. Three patients had a complete remission, and four had a partial remission, according to strict criteria for a response. After treatment, bone-marrow aspirates showed an absence of leukemia cells in three patients and 5 per cent or fewer in three others. Normalization of subnormal peripheral-blood values occurred in six of six patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
159
1
13

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(179 citation statements)
references
References 26 publications
6
159
1
13
Order By: Relevance
“…Up to 90% of patients treated with alpha-interferon (IFN) achieve haematological response, and overall survival reached 85-90% at 5 years (Quesada et al, 1984). More recently, high complete remission (CR) rates have been reported with purine nucleosides (Piro et al, 1990;Spiers et al, 1987;Estey et al, 1992).…”
mentioning
confidence: 99%
“…Up to 90% of patients treated with alpha-interferon (IFN) achieve haematological response, and overall survival reached 85-90% at 5 years (Quesada et al, 1984). More recently, high complete remission (CR) rates have been reported with purine nucleosides (Piro et al, 1990;Spiers et al, 1987;Estey et al, 1992).…”
mentioning
confidence: 99%
“…Discovery of the T-cell receptor in 1982, reported by James Allison, B. McIntyre, & D. Bloch [101] 1984 First report of interferon response in patients with hairy cell leukemia [129] 1991 First report of a human tumor antigen recognized by T-cells, reported by Pierre van der Bruggen, C. Traversari, P. Chomez, et al [36] 1996 Discovery that CTLA-4 blocking antibodies could treat tumors in animal models, reported by Dana Leach, Matthew Krummel & James Allison [72] 1998 Discoveries regarding the activation of innate immunity, by R. Medzhitov, P. Preston-Hurlburt, C. Janeway; & B. Beutler; Beutler awarded Nobel Prize in 2011 [130,131] 2001 Rag2 -/-immunodeficient mice, with no B or T cells, show increased susceptibility to spontaneous and carcinogen-induced tumors, reported by V. Shankaran, with L.J. Old, R. Schreiber, et al [132] 2005 Memory T-cells in colorectal tumors shown to predict clinical outcome, reported by F. Pagès, A. Berger, M. Camus et al [133] 2010 First autologous cell-based cancer vaccine (sipuleucel-T) is approved by the FDA for the treatment of metastatic, asymptomatic stage IV prostate cancer [43,134] 2010 First successful use of gene-edited T-cells for the treatment of CD19+ hematologic malignancies in humans, reported by W. Qasim, H. Zhan, S. Samarasinghe et al [135] 2011 Anti-CTLA-4 (ipilimumab), is the first inhibitory checkpoint inhibitor (ICI) approved by the FDA for treatment of stage IV melanoma [136] 2012 Discovery of the CRISPR/Cas9 system, a simpler and more efficient method of genome editing, reported byJ.A.…”
mentioning
confidence: 99%
“…Quesada et al first documented in 1984 the efficacy of Interferon-alpha (IFN-a) in HCL [35]. Out of the seven patients treated with IFN-a, three achieved a CR and the remaining four achieved a PR.…”
Section: Interferon-alphamentioning
confidence: 99%
“…Large studies comparing the different methods to detect MRD and/or correlating with clinical outcome are lacking. The scenario of CR (MRD+) is different to that of PR in which residual leukemic cells are [35] 1984 2-deoxycoformycin [43] 1984 2-chorodeoxyadenosine [44] 1990 Immuntoxin conjugates [73][74][75][76][77][78][79][80][81][82][83] 2000s…”
Section: Mrd and Adverse Eventsmentioning
confidence: 99%